FERMENTASI ASAM SITRAT DARI TETES TEBU, SECARA BIAK-RENDAM DENGAN Aspergillus niger - Milono Poesponegoro; Oei Ban Liang (Research Center for Chemistry - LIPI, 1991)
A study to determine the optimum condition of !ubmerged. citric acid fermentatlon of calle molasses with Aspergillus niger has been conducted. Effects of the strains of Aspergillus niger, initial concentration of total reducing sugars and initial pH of the medium 011 citric accumulation were investigated. One-stage submerged culture fermentation process was curried out in a 300 ml Erlenmeyer flask which contained 50 ml liquid medium at 30°C, in an orbital shaker incubator operated at 200 rpm. While a two-stage sub-merged [ermen tation process was performed at30Ve in a stirred fermentor containing 2.5 liters of liquid medium at a constant pH, with 1 Will aera, tion and agitation at a speed of 700 rpm. The [ermeutation process was followed by monitoring the changes ill pH values, concentrations of total reducing sugars, dry weight of cellular biomass, and citric acid concentration in the culture medium, during 7 days of [ermentation time. It was obtained that strain of the 1II0uld, concentration of total reducing sugars as well as pH of the medium affected the submerged citric acid fermentation process with Aspergillus niger. Aspergillus niger ATCC 11414 was found to be the best strain aI/lOng the eight strains tested. High initial concentrations of total reducing sugars (15 - 20%) and low initial pH of the medium (less than 3.0) were the optimum conditions for citric acid accumulation by Aspergillus niger ATCC 11414.